The system of measurements of radiation and micrometeorological elements at Mizuho Station, East Antarctica: Installation and performance - Shinji Mae; Makoto Wada; Takashi Yamanouchi (National Institute of Polar Research, 1981)
The Japanese Antarctic Research Expedition operated a three-year project, Polar Experiment South (POLEX-South), from 1979 when the project was limited mainly to the meteorological program, especially the measurements of radiation and vertical profile of temperature and wind in the lowest 30m layer at Mizuho Station (70°42′S, 44°20′E, 2230m above sea level) where katabatic wind blew continuously at a velocity of 12-13 m/s and caused drifting snow. A 30m tower was erected and instrumented in January 1979 and the meteorological program was operational through 1979 and will continue until 1981. The radiation measurements of global shortwave, reflected shortwave, and outgoing and incident longwave were made at the snow surface and at the top of the tower. Direct solar radiation and net radiation were measured only at the snow surface. Temperatures were measured at 15 different levels (7 heights, surface, 7 subsurfaces). Wind velocities and wind directions were measured at 7 levels and 2 levels, respectively. Drifting snow flux, thermal flux in snow, dew point temperature and pressure were also measured. The recording system included a micro-computer, a data logger, transducers, magnetic tape recorders, analog recorders and printing instruments. The measured values were sampled every minute and recorded by magnetic tape recorder and analog recorders. This paper mainly describes the installation and performance of the meteorological system set in a cold katabatic wind area such as Mizuho Station.